Country Partnership Framework for the Oriental Republic of Uruguay for the Period FY16-FY20 - World Bank Group (World Bank, Washington, DC, 2016)
Uruguay is a country of about 3.3 million people, which has consistently given high priority to achieving broadly-shared economic growth and a sustainable reduction in poverty. A strong and progressive social compact has been a defining feature of Uruguayan society and politics, with consistent emphasis placed on protecting vulnerable groups, assuring worker dignity and promoting equitable growth. This compact, combined with rapid economic growth since 2003, has contributed to the development of a sizeable middle class, at 60 percent, the largest in Latin America as a proportion of the population, as well as effective institutions, good governance and, in consequence, a high degree of public trust in Government. The resultant political stability has been a fundamental element of Uruguay’s success in attaining its present standards of living. This Country Partnership Framework (CPF) is aligned with Uruguay’s 2015-2020 political cycle and selectivity has been exercised in the identification of objectives. The design of the CPF program responds to the Government’s priorities and is also closely coordinated with the programs of Uruguay’s other development partners, including IADB and CAF. The program is anchored in the findings of the new Systematic Country Diagnostic (SCD) which was informed by extensive consultations with a wide range of stakeholders. The proposed CPF program is designed to support the Government in its pursuit of six objectives identified in the SCD, grouped into three focal areas, namely, building resilience, rebalancing the social compact, and integrating Uruguay into global markets. During consultations, the Government endorsed the selection of focal areas (CPF’s pillars and objectives) and the technical teams closely coordinated with the Bank experts who designed a set of indicators, which are fully owned.